Diagnosis dan Tatalaksana Aneurisma Aorta Torakalis Dengan Diseksi Tipe Stanford A - A Dimas Wahyu P.H; Setioningsih Diponegoro; Ryan Indra (Riviera Publishing, 2025)
An aortic aneurysm is an abnormal and permanent dilatation of a segment of the aorta with a diameter greater than 1.5 times the normal size. Based on its location, aortic aneurysms are classified as thoracic or abdominal. The incidence of aortic aneurysms, especially abdominal aneurysms, has increased in the last two decades due to aging, increased smoking prevalence, delayed screening, and limited diagnostic tools. This study uses a descriptive case study method to describe the clinical problems in patients. A 60-year-old woman presented to the emergency department (ED) with complaints of fever, nausea, vomiting, and heartburn. The patient had a history of hypertension, dyslipidemia, diastolic dysfunction, and a family history of sudden death suspected to be due to a heart attack. Physical examination revealed cardiomegaly and upper chest pain suspected to be due to aortic dilatation. A chest X-ray showed a mediastinal mass, cardiomegaly, and aortic atherosclerosis. A contrast-enhanced chest CT scan confirmed the diagnosis of thoracic aortic aneurysm with Stanford A/DeBakey II aortic dissection. Initial management includes medication to control blood pressure and other risk factors, while elective surgery is planned as definitive therapy. This case emphasizes the importance of early detection, cardiovascular risk factor control, and multidisciplinary collaboration in the management of aortic aneurysms and dissections to prevent fatal complications.